Implementasi Musyawarah Perencanaan Pembangunan Daerah Rencana Kerja Pemerintah Daerah Kabupaten Kayong Utara Tahun 2021 - Dini Fitrini Utami (JPASDEV : Journal of Public Administration and Sociology of Development, 2021)
This research aimed to describe and analyze the process in the policy implementation of the Community Consultations on Development Planning (musrenbang) for the 2021 North Kayong Regency Regional Government Work Plan (RKPD). Based on the research results, the objectives and the mechanism for implementing the 2021 North Kayong Regency Musrenbang RKPD were not in accordance with the objectives and mechanisms as stipulated in the Minister of Home Affairs Regulation Number 86 of 2017. The quality and quantity of the employees in the Regional Development Planning Agency, Research and Development (Bappedalitbang) as Musrenbang implementers were still low and the policy for  accommodating 1 (one) proposal for Musrenbang per village was only an internal policy of Bappedalitbang.        Based on the foregoing, the writer recommended that the implementation of the Musrenbang RKPD should run more optimally, such as the North Kayong Regency Bappedalitbang that needs to immediately prepare Standard Operating Procedures (SOPs) related to the implementation of the RKPD Musrenbang, encourage improvement in the quality and quantity of human resources at Bappedalitbang, especially the availability of functional  Planners and further enhance effective communication between the legislature and the executive on policies to accommodate community proposals through Musrenbang.